The Management of Channel Health Campaign and the Audience Attitude - Faurani Santi Singagerda, Hasan Basri, Sendi Triwilopo, M. Fikri Akbar, (Opción, 2019)
The aim of the study is to investigate the management of channel health campaign and the audience attitude via explanatory survey method. The results show the same trend with the theory of Planned behavior of Ajzen & Fishbein (1991), that there is an influence of healthy life attitude that contributes to the emergence of healthy life behavior. Attitude and behavior is the effect of persuasion expected from the campaign. In conclusion, implementing a choice of communication channels by ignoring the specific features of audiences in community groups is believed to reduce the effectiveness of health campaigns.